1985
DOI: 10.1007/bf00393506
|View full text |Cite
|
Sign up to set email alerts
|

Carnitine acyltransferases in chloroplasts of Pisum sativum L.

Abstract: Carnitine-acetyltransferase (EC 2.3.1.7) and carnitine-palmitoyltransferase (EC 2.3.1.21) activities were shown to be present in chloroplasts of green pea leaves and possibly to occur in leaf mitochondrial and peroxisomal fractions. A role for the enzymes in the transfer of acyl groups across membranes is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…This acetate could be synthesized in the mitochondria by the combined action of mtPDC and an acetyl-COA hydrolase (Murphy and Stumpf, 1981;Zeiher and Randall, 1990). Also, acetyl-COA could be shuttled directly between the mitochondria and chloroplasts by a camitine/acetyl camitine exchange system across the mitochondrial (Burgess and Thomas, 1986) and chloroplast (McLaren et al, 1985) inner membranes. The low mtPDC to cpPDC capacity found in barley leaves raises the question of whether enough acetyl-COA is produced by mtPDC to provide substrate for both CS and a possible acetyl-COA hydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…This acetate could be synthesized in the mitochondria by the combined action of mtPDC and an acetyl-COA hydrolase (Murphy and Stumpf, 1981;Zeiher and Randall, 1990). Also, acetyl-COA could be shuttled directly between the mitochondria and chloroplasts by a camitine/acetyl camitine exchange system across the mitochondrial (Burgess and Thomas, 1986) and chloroplast (McLaren et al, 1985) inner membranes. The low mtPDC to cpPDC capacity found in barley leaves raises the question of whether enough acetyl-COA is produced by mtPDC to provide substrate for both CS and a possible acetyl-COA hydrolase.…”
Section: Discussionmentioning
confidence: 99%
“…The results rule out the conservation of the thioester bond during acyl export from the plastid, either directly (even if driven by ATP-dependent process to make it directional) or by a "high-energy" intermediate such as acyl-carnitine. An argument has been made that the conservation of the energy of the thioester bond would be preferable during fatty acid export (Thomas et al, 1982(Thomas et al, , 1983McLaren et al, 1985). Countering this argument, it should be noted that the expenditure of an additional ATP in the synthesis of a C18 fatty acid that requires on a molar basis 8 mol of ATP and 16 mol of NAD(P)H for synthesis from acetyl-CoA is not great.…”
Section: Eukaryotic Lipid Synthesis Proceeds With a Hydrolyticmentioning
confidence: 99%
“…Thomas and co-workers have suggested that fatty acyl groups may be exported from the plastid as acyl carnitines (Thomas et al, 1982(Thomas et al, , 1983McLaren et al, 1985). In addition, an acyl-CoA thioesterase was observed with chloroplast envelopes (Joyard and Stumpf, 1980) and was later more specifically localized to the inner envelope (Andrews and Keegstra, 1983;Block et al, 1983).…”
mentioning
confidence: 99%
“…Spots scraped from the TLC plate were counted in 10 ml Optiphase scintillant for 10 min. The identity of the acetylcarnitine spot was con¢rmed by TLC with an authentic standard and by mass spectrometry as described by McLaren et al (1985).…”
Section: (D) Assaysmentioning
confidence: 99%